Peradaban Islam di Nusantara Masa Orde Baru dan Perkembangan Pendidikannya - Ziddan Taufiqul Hakim; Kailatur Rofi’ah; Farihatul Jihan (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
The development of Islamic education in Indonesia during the New Order era and the policies that followed cannot be separated from the nation's historical development and educational policies over time. Islamic education has significantly contributed to shaping the national education system, while its integration into the system has created reciprocal influences between Islamic and national education. During the New Order period (1966–1998)., major changes occurred in Islamic civilization in Indonesia. Although the Soeharto government restricted political Islam through the implementation of Pancasila as the sole ideology, it simultaneously supported the formal development of Islamic education. Indonesia's education system continued to experience a dualistic structure separating general and religious education, a condition inherited from the Dutch colonial period. This study aims to examine the development of Islamic education, the role of Islam in Indonesia, and educational policies during the New Order era. Using a literature review approach, the findings indicate that education was a primary concern of Indonesian Muslims from the early spread of Islam. However, educational policies were often influenced by political interests. Therefore, educational policy should remain independent of political intervention to achieve educational objectives and produce high-quality future generations.